Structural Embedded Ties between Fharmaceutical Companies’ Representatives and Practitioners: the Threat of Dissolution - Анастасия Александровна Маркова (Journal of Economic Sociology, 2010)
Russian pharmaceutical market, which took the place of the Soviet centralized system of health care, has changed dramatically. First of all, these changes are caused by the state trying to improve legal regulation in the field of drug turnover. Apart from changes in pricing methods for drugs, clinical trials procedures and licensing, and state expert system, Russian Ministry of Health and Social Development is planning to make Federal law amendments to constrain relationships between medical companies’ representatives and physicians. A peculiarity of personal selling methods on pharmaceutical market is that medical representatives are not involved into direct sales of drugs but significantly influence the ultimate demand by providing intermediate consumers (medical or pharmaceutical staff) with personal information. Medical representatives’ behaviour is not only economic and they are not just atomized actors in this market; their relationships with physicians can be based on trust, reliable information and joint problem-solving arrangements [Uzzi 1996] conditioning coherence and interdependence.The author studies relationships between medical representatives and physicians from the structural embeddedness perspective. Based on the research she discloses the existing practices of relationships between pharmaceutical companies and physicians, describes possible ways of resolving administrative and legal problems associated with new regulations of drug turnover. The author also gives attention to the dissolution of ties as an important element of network analysis